Temperature and Air Velocity Simulation on Sago Starch Pneumatic Conveying Recirculated Dryer Using Ansys Fluent - Abadi Jading; Nursigit Bintoro; Lilik Sutiarso; Joko Nugroho Wahyu Karyadi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2018)
Pneumatic Conveying Recirculated Dryer (PCRD) is one of many driers used for drying wet sago starch. The most important components of this PCRD machine are the vertical pipe and the u-bend. The vertical pipe and the u-bend are the primary drying spaces. They must have a good temperature distribution and air velocity dryer. To observe the process of temperature distribution and the air velocity dryer in the vertical pipe and u-bend, Computational Fluid Dynamics (CFD) analysis is required. The research was aimed to analyze the temperature distribution and the air velocity dryer flow in the recirculated pipe of PCRD machine by using CFD analysis. The analysis was based on the variance of the temperature, the air velocity, and the height of the vertical pipe in PCRD machine. The analysis was conducted using Ansys Workbench Fluid Flow ver. 15. This software was used to simulate the temperature and the air flow velocity in the vertical pipe and the u-bend. However, the flow characteristics and patterns of the wet sago starch were not included in the discussion. The turbulence model used in the simulation was the Reynold Stress Models (RSM). The result of the simulation showed that the temperature along the vertical pipe and the u-bend was distributed evenly. The error value between the result of the simulation and the observation was low (0.10–2.04%). The average test value with paired t-test showed that the simulation and observation result was not significantly different. This results indicated that the simulation fit well with the observation value or the real condition in the PCRD machine. The distribution of the temperature and the air velocity dryer in the vertical pipe and the u-bend were able to reduce the moisture content on sago starch from 31% (wb) to 9% (wb). Therefore, the vertical pipe and the u-bend design was appropriate to use in PCRD machine for drying wet sago starch.